Pemberdayaan Perempuan Melalui Microfinance :Suatu Telaah Kebijakan Penanggulangan Kemiskinan - Aryo, Bagus (Jurnal Ilmu Kesejahteraan Sosial, 2006)
Woman is an adequate partner to microfinance because not only assisting women but also their families and society. There’re some challenges and constraints faced by women related to microenterprises such as norm, cultural, mobility, lameness gender, work without “payment" in household, high number of illiterate, etc. Some characteristics of microenterprises managed by women: Informal; Home-based business; Concentration on low return sectors; Oriented on conservative growth; Part-Time and depend on season; and Lac of technology. There’re some dimensions of women empowering: women prosperity such food, income and health care also women access to production factors; Conscientisation is understanding to sex and gender role;